KEANEKARAGAMAN JENIS MAMALIA DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG, SULAWESI SELATAN - Mustari, Abdul Haris; Surono, Hadi; Mansyur, Fadhilah Iqra (Media Konservasi, 2016)
Bantimurung-Bulusaraung National Park is the largest karst-ecosystem in Indonesia. Situated in the centre of Wallacea-Bioregion, the national parkhas significance role as stonghold of many species taht are endemic to this biodiversity’s hot spot.  This study aims to reveal mammals’diversity in the national park.  The study was conducted from February to March 2011. At leat  12 species consisting of 9 family of mammals recorded in the national park including the endemic and rare species such as Sulawesis’s Moore Macaque Macaca maura, Sulawesi’s Bear Cuscus Ailurops ursinus, Sulawesis’s Dwarf Cuscus Strigocuscus celebensis, and Tarsier  Tarsius fuscus. Keywords: Mammals, diversity, conservation, national park.